Minimal change disease associated with malignant pleural mesothelioma: case report and review of the literature. (19th December 2016) - Yildiz, Halil; Andreea, Stoian Ioana; Hoton, Delphine; Cyr Yombi, Jean
Abstract : A 77-year-old man with a history of asbestos exposure was admitted to our internal medicine division for generalised weakness, fatigue, loss of weight, night sweats and difficulty for breathing since 3 months. Clinical examination revealed left fine crackles and bilateral leg oedema. Blood test showed elevated C reactive protein level at 142 mg/L, lactate dehydrogenase level at 421 UI, creatinine level at 5.75 mg/dL. Serum albumin level at 30 g/L, urinalysis showed significant proteinuria at 6.4 g/L. Chest X-ray showed left pleural effusion. Renal ultrasonography was normal. Thoracic CT and positron emission tomography showed mediastinal enlargement with lymphadenopathies and left pleural effusion and thickening. A pleural biopsy showed features compatible with malignant epithelioid mesothelioma. Renal biopsy showed minimal change disease and acute tubular necrosis. A diagnosis of malignant mesothelioma associated with minimal change disease and acute tubular necrosis secondary was then made. Given the poor general condition, palliative care was initiated and the patient died from respiratory failure 3 months later.